2021
DOI: 10.3390/pathogens10091114
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan and Microbial Pathogens of House Cats in the Province of Tekirdag in Western Turkey

Abstract: Domestic felines' re-emerging infectious and neglected zoonotic diseases are a significant focus of global "One Health" efforts. This study aimed to rapidly diagnose 14 pathogens, including zoonoses by using PCR primers in 167 client-owned symptomatic cats, routinely accepted to the Veterinary Clinics of Tekirdag. The prevalence of pathogens investigated were as follows: Babesia canis canis (24%), Babesia microti (2.4%), Hepatozoon felis (10.8%), Cytauxzoon felis (6.6%), Bartonella henselae (40.1%), Anaplasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 97 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…However, our correlation of bacterial prevalence with age was in contrast to a prevalence study in house cats in Western Turkey. In this study, Muz et al reported that there was no statistical difference observed between the prevalence of the pathogen in different age groups [ 7 ]. Furthermore, in our study, the most commonly isolated species of bacteria were E. coli , S. felis , Enterococcus spp., and P. mirabilis in cats, which agreed with the findings of Jung et al in stray and hospital admitted cats of South Korea [ 8 ].…”
Section: Discussionmentioning
confidence: 56%
“…However, our correlation of bacterial prevalence with age was in contrast to a prevalence study in house cats in Western Turkey. In this study, Muz et al reported that there was no statistical difference observed between the prevalence of the pathogen in different age groups [ 7 ]. Furthermore, in our study, the most commonly isolated species of bacteria were E. coli , S. felis , Enterococcus spp., and P. mirabilis in cats, which agreed with the findings of Jung et al in stray and hospital admitted cats of South Korea [ 8 ].…”
Section: Discussionmentioning
confidence: 56%
“…Map was created utilizing mapchart.net. Prevalence is derived from the following manuscripts: Albania [ 48 ], Australia [ 22 , 49 ], Brazil [ 40 , 50 55 ], Canada (British Columbia [ 56 ], Ontario [ 18 ], Saskatchewan [ 57 ], Prince Edward Island [ 58 ]), Chile [ 59 ], China [ 60 ], Cyprus [ 61 ], Denmark [ 62 ], Ecuador [ 63 ], Egypt [ 64 ], Germany [ 17 , 65 ], Greece [ 66 , 67 ], Iran [ 68 ], Ireland [ 69 ], Italy [ 25 , 45 , 70 72 ], Kenya [ 29 ] Japan [ 46 , 73 , 74 ], New Zealand [ 75 ], Portugal [ 32 , 76 ], Qatar [ 77 ], Romania [ 78 ], Russia [ 79 ], Saudi Arabia [ 80 ], South Africa [ 81 ], South Korea [ 82 ], Spain [ 40 , 83 , 84 ], Switzerland [ 19 ], Tanzania [ 28 ], Thailand [ 28 , 85 – 87 ], Turkey [ 88 , 89 ], Trinidad and Tobago [ 90 ], England [ 91 ], USA (Arizona [ 92 ], California, Colorado, and Florida [ 93 ], Louisiana [ 94 ], and Virginia and North Carolina [ 23 ]), Scotland [ 95 ], and Singapore […”
Section: Discussionmentioning
confidence: 99%
“…Of interest, the Philippines had the highest Bartonella spp. prevalence (61.3%) [43], followed by Turkey (40.1%) [71], Korea (33.6%) [72,73] and Israel (28.6%) [3,74]. Furthermore, other studies reported lower Bartonella prevalence rates varying between 9.1% and 19.6% in China [69,[75][76][77], Thailand [78][79][80][81], Saengsawang et al [82], Taiwan [83,84], Malaysia [85], Japan [86]; Sato et al [87], Saudi Arabia [88].…”
Section: Discussionmentioning
confidence: 99%